TRANSFORMASI PELAYANAN SERTIPIKAT ELEKTRONIK DI KANTOR PERTANAHAN KOTA PEKANBARU TAHUN 2023-2024 - Putri, Dienda Radya; Febrina, Rury (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Digital transformation in public services has become a primary focus of the government to enhance efficiency, transparency, and accountability within the bureaucracy. One notable form of this transformation is the implementation of electronic land certificates by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN), including at the Land Office of Pekanbaru City. This study aims to analyze the transformation carried out by the government in providing electronic certificate services and to evaluate its impact on the quality of land services from 2023 to 2024. The analysis is based on the transformation theory that emphasizes four key aspects mindset transformation, structural transformation, empowerment, and renewal. This research employs a descriptive qualitative method, with data collected through interviews and document studies. The data are analyzed using the transformation theory proposed by Gouillart and Kelly, focusing on the four aforementioned dimensions, aimed at improving service efficiency, transparency, and accountability. The findings indicate that the transformation of land services through digitalization has facilitated easier access, accelerated administrative processes, and reduced land-related fraud and mafia practices. However, several challenges remain, including technological infrastructure readiness, public digital literacy, and resistance from certain stakeholders. This study recommends enhancing human resource training, strengthening data security systems, and conducting more extensive public outreach to optimize the implementation of electronic land certificates. Furthermore, it is suggested to develop a decentralized data validation application that does not rely solely on a centralized master system. To improve land data quality, collaboration with local sub-district and village offices is also recommended to accelerate data validation processes, thereby supporting the effective issuance of electronic land certificates in the future. Keywords: Public Service, Electronic Certificate, Service Transformation.